Development of E-Learning Content by Lab Rotary Inquiry Learning on Support Solution Materials for Senior High School - Nadia Marsila; Dara Juliana; Rifa Aisyah; Nurul Amini; Eko Nevriansyah (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2022)
Chemistry as an everyday science, students first need to understand everyday chemistry. Inquiry learning is a learning model in which students acquire the necessary knowledge through direct thinking, questioning, inquiry or research, experimentation or independent research. This study aims to help high school students understand chemistry learning during the Covid-19 pandemic. The study was conducted using a research and development (R & D) model using a 4D development model. Verification of e-learning products was performed by two chemistry teachers using Kappa Cohen's analytical formula. Content validity and composition validity are in a very high range, with k values ​​of 0.87 and 0.84. The program performance k-value is in the very high category of 0.82, and the last aspect is the e-learning design and the very high k-value category of 0.84. Based on the results of the data analysis, we can conclude that e-learning is effective and can be used in the learning process.